Prospecção da utilização de hidrolisado proteico de castanha-do-brasil no enriquecimento nutricional de biscoitos com adição de farinha de pupunha - Bernardi, Delma Pereira da Silva (Universidade Federal do Tocantins, 2024)
The legal Amazon stands out for containing a diversity of fruits with high nutritional value with prospects for industrial application. The study of this biome is of great importance for the renewal of knowledge, in addition to adding value to the flora of this region. From peach palm fruits, a flour with high nutritional value, rich in bioactive compounds, is obtained. The application of this food matrix in the development of new products can represent an important strategy for the dissemination and consumption of these compounds. In addition to the peach palm, the Brazil nut (Bertholletia excelsa, H.B.K) is an important species of extractive exploitation native to the Amazon and industrially benefited. From the extraction of its oil, a co-product called cake with high nutritional value and functional properties is obtained. This cake is a source of vegetable protein that can be used, for example, in the preparation of protein hydrolyzate. Protein hydrolysates can be used in various products, including bakery products. In view of this, aiming at the use of Amazonian fruits, as well as their feasibility of use in the development of food products, the objective of this study was to explore the use of protein hydrolyzate from Brazil nut cake in the nutritional enrichment of cookies with added of peach palm flour. Initially, the process of obtaining the hydrolyzate was optimized, which was characterized in terms of its nutritional properties, antioxidant activity and techno-functional properties. A flour was obtained from peach palm fruits and its nutritional, technological characteristics and antioxidant activity were evaluated. Subsequently, different biscuit formulations were prepared with the addition of protein hydrolyzate and peach palm flour, and the nutritional quality, mineral profile and antioxidant activity of the formulations were evaluated. It is concluded that peach palm flour, like Brazil nut pie, has high nutritional quality. In the flour, the high carbohydrate content (75.65%), energy value (378.94) and carotenoid content (2980.00 μg/100g) stood out, while in the pie the high protein content (35.00 μg/100g) stood out. 99%), lipids (37.84%) and ash (4.49%). Brazil nut cake proved to be a good substrate for the production of protein hydrolyzate when subjected to an enzyme concentration of 1.0% (E/S) at a temperature of 60 ºC for 120 minutes. The protein hydrolyzate obtained proved to be effective in neutralizing free radicals, in addition to having a high protein content (46.34%) and containing all essential amino acids. The cookies produced presented very interesting nutritional characteristics, such as a high content of proteins, total carotenoids, iron and zinc.